Transvenous embolization of a pediatric pial arteriovenous fistula. (7th July 2011) - Cooke, Daniel; Tatum, James; Farid, Hamed; Dowd, Christopher; Higashida, Randall; Halbach, Van
Abstract : Pial arteriovenous fistulas (AVFs) are a rare, although clinically significant, vascular anomaly affecting the pediatric population. There are few retrospective case series describing their epidemiological, clinical and radiographic characteristics as well as technical elements of treatment. Combined transarterial and transvenous embolization of a 12 month old female with a multi-hole pial AVF is described. The patient underwent treatment in a staged fashion and without neurological complication.